DESIGN OF LIGHTWEIGHT CHASSIS UNDER STATIC LOAD, DYNAMIC LOAD, AND FRONTAL IMPACT - Wisnu Aprialdi, Setya
One type of vehicles that have a large number of victims are bus. Conventional bus vehicles with Internal Combustion Engine (ICE) fuel have a negative influence, that is air pollution. Air pollution can be reduced by changing transportation modes to electric bus vehicles. This study aims to redesign the steel-based electric bus chassis into an aluminum extrusion aluminum-based electric bus chassis, which can withstand the static operating, dynamic and frontal impact. In this study, redesigned electric bus chassis based on extruded aluminum material was carried out. Then static, dynamic and frontal impact simulations are performed. The simulation is done using numerical computation based on finite element method, then the model is validated by comparing the simulation results with the experiments. After static, dynamic and frontal impact loading simulations, an aluminum chassis design that meets the criteria of the three analyzes is obtained, namely the design of a square channel cross-section aluminum chassis with a thickness of 5 mm. From the static load simulation, Von-Mises stress value is 87.43 MPa, which is 32% lower than the strength of the aluminum, when the chassis receives maximum operating load the chassis is still safe. From the natural frequency simulation, the value of the natural frequency of the aluminum chassis in the first 10 modes is greater than the steel chassis, which is the aluminum chassis is stiffer than the steel chassis. From the frontal impact simulation, obtained battery deformation in the aluminum chassis of 2.7 mm where the safety limit is 6 mm. If the aluminum chassis is compared to a steel chassis that weighs 328 kg, the aluminum chassis weighs 154 kg which is 47% lighter than the aluminum chassis. Thus, it is expected that this research can reduce the cost of manufacture and improve vehicle efficiency while still paying attention to aspects of structural safety.